SPIRITUAL AND MORAL DIRECTIONS OF PREPARING SCHOOL STUDENTS FOR INTERETHNIC DIALOGUE - Ostonov Jasur Shopirjonovich; Ernazarova Zulxumor Mukhammadi qizi (Web of Journals Publishing, 2025)
In our developing society today, the number of people engaged in scientific activities is large. In particular, writers of scientific articles. Writing articles serves both the career and the position of each scientist and also shows that he is a high-level representative of his field in the future. This article provides information about the spiritual and moral directions of preparing schoolchildren for interethnic dialogue.
Keywords: Culture, spiritual, moral, pedagogical and psychological, interethnic relations, education, students, nation, spirituality, people.